Responsible living concepts, education and future perspectives - Thoresen, Victoria W. (Springer, 2015)
"Focusing on the challenges of the transition to responsible, sustainable lifestyles, this book examines developments over the last decade in relation to: the creation of awareness of consumer citizenship, civic involvement and environmental stewardship ; research, projects and publications on education for responsible living ; the creation and implementation of relevant teaching methods and materials ; policies on education for sustainable consumption and lifestyles ' ; and global processes for education on sustainable development"--Provided by publisher.